Qat Chewing and Periodontal Pathogens in Health and Disease: Further Evidence for a Prebiotic-Like Effect - Al-Alimi, A.; Taiyeb-Ali, T.; Jaafar, N.; Al-Hebshi, N.N. (Hindawi Publishing Corporation, 2015)
Aim. Qat chewing has been reported to induce subgingival microbial shifts suggestive of prebiotic-like properties. The objective here was to assess the effect of qat chewing on a panel of classical and new putative periopathogens in health and periodontitis. Materials and Methods. 40 qat chewers and 40 nonchewers, equally stratified by periodontal health status, were recruited. Taqman, real-time PCR was used to quantify total bacteria, Porphyromonas gingivalis, Tannerella forsythia, Treponema denticola, Parvimonas micra, Filifactor alocis, Synergistetes, and TM7s in pooled subgingival biofilm samples. Differences in microbial parameters between the study groups were analysed using ordinal regression. Results. In health, the qat chewers harboured significantly lower relative counts of P. gingivalis, T. forsythia, Synergistetes, and TM7s after adjustment for multiple comparisons (). At nominal significance level, they also carried lower counts of TM7s and P. micra (). In periodontitis, the chewers had lower counts of all taxa; however, only T. denticola withstood correction for multiple comparisons (). Conclusions. Qat chewing is associated with lower proportions of periopathogens, particularly in subjects with healthy periodontium, which supports previous reports of its prebiotic-like properties. This potentially beneficial biological effect can be exploited by attempting to isolate the active fraction.